SAMIRAN DAM PERFORMANCE ANALYSIS BASED ON THE CRITERIA FOR EVALUATION OF BUILDING FUNCTIONS AND STRUCTURES USING THE AHP METHOD IN PAMEKASAN REGENCY - Zabadi Fairus (Journal Innovation of Civil Engineering (JICE), 2022)
The purpose of the author conducting this research is a follows: (1) as a criterion for determining the condition of the existing weir and an assessment of the function of the weir according to the existence of the building, (2) to obtain the value of the components of the weir building so that it can be used in weir work on the existence and function of the building. , (3) to analyze the results of the work of the dam on the Samiran Embankment allocated in Pamekasan Regency to the existence and function of the dam building. The current study raises the subject of the Samiran Dam which is located in Samiran, a remote village from one of the sub-districts located in the middle of Pamekasan Regency, East Java Province. Methods for collecting data can be obtained from direct surveys in the field, so that from these results the data is then processed. The next step, the existence and purpose of the construction of the Samiran weir can be analyzed according to the initial concept. The method used is AHP. From analyzing and then collecting weir data which aims to obtain work from the weir and the presence of damaged weir components in the form of discharge strength of 18.89%, presence of sediment 1.25%, lighthouse 0.19%, extraction building 2.56%, drainage building 4.26%, flushing buildings 1.88%, and mud bags 4.15%. The following are the results of analyzing the work of the weir according to the use of weir components, namely discharge 32.92%, sediment 3%, lighthouse 2.39%, intake building 14.29%, draining building 21.14%, flushing building 21.14%, and mud bag 9.86%. From the results above, it can be assumed that the component of the work of the dam on the Samiran reservoir is 33.18% damaged with the position of the weir being slightly damaged. Meanwhile, the usefulness of the weir work on the Samiran reservoir is 93.31% and the condition of the weir is fine.